2019
DOI: 10.4236/ajibm.2019.99121
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emotional Intelligence on Readiness for Organizational Change: A Case Study on a Government Authority in Saudi Arabia

Abstract: This study sought mainly to examine the effect of Emotional intelligence (EI) and readiness for organizational change (RFC). Additionally, the study sought to explore the association between EI, RFC and demographic variables. The data were collected from employees from a government authority in Jeddah city, Saudi Arabia. The data were analyzed using Spearman's rho to find the relation between EI and employee's RFC. Then, Simple Linear Regression was applied to find the effect of EI on the employee's RFC. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…According to the findings of a regression study by Moradi et al (2012), emotional intelligence shows a substantial inverse correlation with resistance to change. A similar finding in the study of Alzahrani (2019) revealed that emotional intelligence has a significant and positive effect on readiness to change. Therefore, based on the available background, the following hypothesis can be proposed:…”
Section: Emotional Intelligence and Resistance To Changesupporting
confidence: 83%
See 1 more Smart Citation
“…According to the findings of a regression study by Moradi et al (2012), emotional intelligence shows a substantial inverse correlation with resistance to change. A similar finding in the study of Alzahrani (2019) revealed that emotional intelligence has a significant and positive effect on readiness to change. Therefore, based on the available background, the following hypothesis can be proposed:…”
Section: Emotional Intelligence and Resistance To Changesupporting
confidence: 83%
“…Change has become an ongoing process for organizations in today's competitive world as a result of ever-changing external conditions such as technological advancements, international pressures, and market conditions (Amarantou et al, 2018); Georgalis et al (2015). An increasing number of people are realizing that greater attention has to be given to globalization and competitiveness that forces companies to respond to changing business structures, laws, or regulatory structures continuously and use advantages as soon as possible (Noe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%